Flavonoids isolated from Dipterocarpus obtusifolius - Toan Phan, Nguyen Huu; Dieu Thuan, Nguyen Thi; Duy, Nong Van; Mai Huong, Pham Thi; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Thanh, Nguyen Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Five flavonoids including tiliroside (1), kaempferol 3-O-(2¢¢,6¢¢-di-O-(E)-p-coumaroyl-β-D-glucopyranoside) (2), myricetin (3), myricitrin (4), and myricetin 3-O-α-arabinofuranoside (5) have been isolated and identiﬁed from the leaves of Dipterocarpus obtusifolius. Their chemical structures were elucidated by spectroscopic methods including NMR and MS, and by comparison with the literature data. All these compounds were isolated from this plant for the first time.